The LOTUS domain is a conserved DEAD-box RNA helicase regulator essential for the recruitment of Vasa to the germ plasm and nuage - Jeske, Mandy; Müller, Christoph W.; Ephrussi, Anne (Genes & development, 2017)
Jeske et al. show that LOTUS domains present in the germline proteins Oskar, TDRD5, and TDRD7 bind and stimulate the germline-specific DEAD-box RNA helicase Vasa. In vivo, the localization of Drosophila Vasa to the nuage and germ plasm depends on its interaction with LOTUS domain proteins., DEAD-box RNA helicases play important roles in a wide range of metabolic processes. Regulatory proteins can stimulate or block the activity of DEAD-box helicases. Here, we show that LOTUS (Limkain, Oskar, and Tudor containing proteins 5 and 7) domains present in the germline proteins Oskar, TDRD5 (Tudor domain-containing 5), and TDRD7 bind and stimulate the germline-specific DEAD-box RNA helicase Vasa. Our crystal structure of the LOTUS domain of Oskar in complex with the C-terminal RecA-like domain of Vasa reveals that the LOTUS domain occupies a surface on a DEAD-box helicase not implicated previously in the regulation of the enzyme's activity. We show that, in vivo, the localization of Drosophila Vasa to the nuage and germ plasm depends on its interaction with LOTUS domain proteins. The binding and stimulation of Vasa DEAD-box helicases by LOTUS domains are widely conserved.